TLS. Link a dynamic hybrid real-time reconfigurable transmission line simulator (Software Component) - Santonia, Gerald V. (2007)
The computer has been a powerful tool for simulation and has replaced most hardware simulators for the power system. However, software simulation is abstract in nature. To better understand the behavior of the power system, there is a need to bring out the voltages and currents to physical meter and control devices. TLS.Link is a project dynamically simulates single-phase transmission line behavior through an integrated software/hardware simulator. An Electromagnetic Transients Program (EMTP) was created to simulate the behavior of the power system modeled in the computer. The simulated voltages and currents were exported from the computer to the power conditioning and amplification circuits to make the voltages and currents available to various power system hardware. This paper documents the implementation of the software component of TLS.Link. With the user providing the input system parameters, the EMTP computers for the power system voltage and current values during steady state and transient condition. Transient condition results from a fault occurrence triggered by a time specified by the user. The program generates a current waveform that were sent to the serial port as an input to the hardware component of TLS.Link. This project serves as the foundation to develop a micro-controller-based transmission line simulation for the eventual creation of economical real-time reconfigurable hybrid simulator for larger power system and real-time load flow applications.